2018
DOI: 10.1080/00223980.2018.1446894
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style, Perceived Loneliness, and Psychological Well-Being in Smoking and Non-Smoking University Students

Abstract: The growing rate of smoking cigarettes among the youths necessitates examining its contributing factors. Accordingly, we aimed to compare smoking and nonsmoking university students in their attachment styles, perceived loneliness, and psychological well-being. To this end, we recruited 100 current smokers and 100 nonsmoking students by using a convenience sampling method from Shahid Beheshti University, Tehran, Iran. All participants completed the Adult Attachment Scale, Loneliness Scale, and General Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…A secure attachment style, increased age, and higher house crowding index were associated with lower cigarette smoking addiction in adolescents, as opposed to insecure attachment styles (preoccupied, dismissing, and fearful) and female gender, in line with previous research [18,82]. Indeed, people with insecure attachment styles have low selfesteem and more anxiety, which increase substance abuse, such as smoking, especially in cases of emotional distress [83].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A secure attachment style, increased age, and higher house crowding index were associated with lower cigarette smoking addiction in adolescents, as opposed to insecure attachment styles (preoccupied, dismissing, and fearful) and female gender, in line with previous research [18,82]. Indeed, people with insecure attachment styles have low selfesteem and more anxiety, which increase substance abuse, such as smoking, especially in cases of emotional distress [83].…”
Section: Discussionsupporting
confidence: 84%
“…Previous findings suggest that smokers were more likely to be of the anxious type [17]. Indeed, young adults who tend to smoke have more conflicts within their families and are, therefore, influenced by external objects, such as cigarettes to overcome their psychological needs [18], but to our knowledge, no studies have shown an association between waterpipe addiction in adolescence and attachment styles.…”
Section: Introductionmentioning
confidence: 78%
“…It is hypothesized that these older adolescents may have a higher awareness of the health consequences of smoking than younger adolescents [51]. In addition, higher house crowding index was associated with lower smoking addiction in adolescents, in line with previous research [53,54]. This negative association can be hypothesized by the fact that a crowded house does not give to adolescent's freedom or the time to smoke alone, especially if their roommate is annoyed by passive smoking [32].…”
Section: Sociodemographic Characteristicssupporting
confidence: 74%
“…Several studies reported that loneliness negatively impacted psychological adjustment and well-being Houghton et al, 2016;Mellor et al, 2008;Tanhan, 2020). Among university students, loneliness was significantly found to be associate with anxiety and depressive symptoms (Kim et al, 2017;Moeller & Seehuus, 2019;Richardson et al, 2017;Tanhan, 2020), aggressive behaviors (Yavuzer et al, 2019), psychological well-being (Doman & Le Roux, 2012;Satici, 2019), and addictive behaviors (Habibi et al, 2018;Skues et al, 2016). Further, some research investigated the association between loneliness and a variety of outcomes during the coronavirus pandemic.…”
mentioning
confidence: 99%